2018
DOI: 10.3233/jad-170713
|View full text |Cite
|
Sign up to set email alerts
|

Supplemental Retinal Carotenoids Enhance Memory in Healthy Individuals with Low Levels of Macular Pigment in A Randomized, Double-Blind, Placebo-Controlled Clinical Trial

Abstract: This randomized, double-blind, placebo-controlled clinical trial demonstrates a memory-enhancing effect of daily supplementation with L, Z, and MZ in healthy subjects with low MP at baseline. The implications of these findings for intellectual performance throughout life, and for risk of cognitive decline in later life, warrant further study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
64
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(69 citation statements)
references
References 90 publications
2
64
1
2
Order By: Relevance
“…The authors concluded that a higher intake of carotenoids, both from food and supplements, correlated significantly with better mental performance. These positive effects were confirmed in a randomized, double-blind placebo-controlled study by Power et al [78]. This study involved 91 persons with an average age of 45 years, who received either a supplement containing lutein (10 mg), zeaxanthin (2 mg), and meso-zeaxanthin (10 mg) or placebo for 12 months.…”
Section: Carotenoidsmentioning
confidence: 83%
“…The authors concluded that a higher intake of carotenoids, both from food and supplements, correlated significantly with better mental performance. These positive effects were confirmed in a randomized, double-blind placebo-controlled study by Power et al [78]. This study involved 91 persons with an average age of 45 years, who received either a supplement containing lutein (10 mg), zeaxanthin (2 mg), and meso-zeaxanthin (10 mg) or placebo for 12 months.…”
Section: Carotenoidsmentioning
confidence: 83%
“…Seven trials fulfilled the inclusion criteria of this systematic review, and all included studies had parallel designs (Table 1). Two studies [20,28] were performed as sub-studies of clinical trials that investigated the effects of macula carotenoid intake for improvement in visual function in a normal population and prevention of age-related macular degeneration.…”
Section: Included Studiesmentioning
confidence: 99%
“…The mean age of participants ranged from 21.21 to 73.74 years. Among the seven studies, one study included young college students [29], three studies included middle-aged adults (aged 40-60 years) [20,30,31], and three studies included elderly individuals (aged over 60 years) [21,28,32]. Four of the trials were conducted in the United States [21,28,29,32], two in Japan [30,31], and one was conducted in Ireland [20].…”
Section: Participantsmentioning
confidence: 99%
See 2 more Smart Citations